(untitled) (Research, Society and Development, 2022)
The industrial age caused several repercussions in the historical and educational context, the capitalist society centered on consumption, production and work, raised the need for schooling centered on technical foundations, starting from a teaching centered on teachers in the molds where knowledge is transmitted from teacher to teacher. the student. This model, which had the purpose of forming citizens submissive to the labor market, was associated with traditional education over many decades. The Escola Nova or Escolanovismo movement emerged in the late 19th and early 19th centuries from various criticisms of the school context in view of the decontextualization of teaching, traditional teaching, as well as banking education and focused exclusively on work. This movement was essential for a sensitive look at the importance of contextualization in activist, progressive and reality-changing teaching. Embracing these assumptions, the 21st century guides a mediation of teaching to digital natives from the insertion of digital media, digital technologies and digital resources in the classroom, a challenge for both management, teachers and employees in general in the adaptive assumption. Therefore, this research aimed to reflect on the insertion of digital technologies in the school context from the perspective of digital literacy. The results infer that students in the digital age are attracted by the insertion of the internet, cell phones and other technologies in the teaching and learning processes. Furthermore, the school curriculum still needs to incorporate and apply new trends in digital literacy as a result of advances in technology in the construction of knowledge. In addition, pedagogical resources have expanded and, with the support of digital technologies, interaction and engagement in initial and continuing training have increased their importance in pedagogical practices.